Kualitas Pelayanan dan Loyalitas Anggota Koperasi Syariah di Indonesia - Umuri, Khairil; Nurdin, Ridwan; Haris Riyaldi, Muhammad (STAI Terpadu Yogyakarta, 2023)
Cooperative members are the most crucial part of the activities conducted by cooperatives. Cooperatives also contribute to realizing economic prosperity, both for their members and the surrounding community. The purpose of this research is to examine the relationship between service quality and the loyalty of members of sharia cooperatives in Indonesia. The research was conducted using a qualitative method with a literature review approach. The results show that the aspect of service quality has a significant influence on the loyalty of members of sharia cooperatives in Indonesia. This phenomenon is evident in several Islamic cooperatives in Indonesia, reflecting a positive relationship between service quality and member loyalty. The research findings are expected to serve as a guide and consideration for sharia cooperatives and stakeholders in their efforts to retain members and encourage them to continue using the services of sharia cooperatives.